A Tool for Investigating Asthma and COPD Exacerbations: A Newly Manufactured and Well Characterised GMP Wild-Type Human Rhinovirus for Use in the Human Viral Challenge Model. - Daniel J Fullen; Bryan Murray; Julie Mori; Andrew Catchpole; Daryl W Borley; Edward J Murray; Ganesh Balaratnam; Anthony Gilbert; Alex Mann; Fiona Hughes; Rob Lambkin-Williams (PLoS ONE, 2016)
Human Rhinovirus infection is an important precursor to asthma and chronic obstructive pulmonary disease exacerbations and the Human Viral Challenge model may provide a powerful tool in studying these and other chronic respiratory diseases. In this study we have reported the production and human characterisation of a new Wild-Type HRV-16 challenge virus produced specifically for this purpose.A HRV-16 isolate from an 18 year old experimentally infected healthy female volunteer (University of Virginia Children's Hospital, USA) was obtained with appropriate medical history and consent. We manufactured a new HRV-16 stock by minimal passage in a WI-38 cell line under Good Manufacturing Practice conditions. Having first subjected the stock to rigorous adventitious agent testing and determining the virus suitability for human use, we conducted an initial safety and pathogenicity clinical study in adult volunteers in our dedicated clinical quarantine facility in London.In this study we have demonstrated the new Wild-Type HRV-16 Challenge Virus to be both safe and pathogenic, causing an appropriate level of disease in experimentally inoculated healthy adult volunteers. Furthermore, by inoculating volunteers with a range of different inoculum titres, we have established the minimum inoculum titre required to achieve reproducible disease. We have demonstrated that although inoculation titres as low as 1 TCID50 can produce relatively high infection rates, the optimal titre for progression with future HRV challenge model development with this virus stock was 10 TCID50. Studies currently underway are evaluating the use of this virus as a challenge agent in asthmatics.ClinicalTrials.gov NCT02522832.